Effect of Retention of Results on Patient Satisfaction with Orthodontic Treatment - Anton Timoshin (Journal of Global Pharma Technology, 2020)
Currently, the number of requests for orthodontic care has increased significantly. This is facilitated by a number of factors -the technical capabilities of orthodontists, which have grown many times due to technological progress and the ability to provide the necessary assistance at almost any age; the need for an aesthetic result, which is formed under the influence of the media. As a result, there are high requirements for both yourself and your appearance, as well as for the orthodontist. Thanks to new technologies, such as cortical support, it became possible to solve the treatment of dental anomalies, which previously could only be cured by surgery. But at the same time, such an important issue as the retention of the results achieved remains open. We studied the objective parameters that changed as a result of orthodontic treatment (teleradiography orthopantomography, analysis of control and diagnostic models), and compared them with the subjective assessment of patients. We have found that the patient's motivation, desire to cooperate with the doctor, a clear understanding of the treatment goals allows you to get a high-quality result and keep it for a long enough period of time. Keywords: dental anomalies, orthodontic treatment, bracket system, period of retention, treatment planning.